The role of the church in ending female genital mutilation/cutting in order to promote the flourishing of women : a case study of the Wolaita Kale Heywet Church, Southern Ethiopia - Dora, Tihitina Telemos (Stellenbosch : Stellenbosch University, 2018)
Thesis (MTh)--Stellenbosch University, 2018.